2015
DOI: 10.1038/hr.2015.66
|View full text |Cite
|
Sign up to set email alerts
|

Chronic arterial hypertension impedes glioma growth: a multiparametric MRI study in the rat

Abstract: Glioblastoma is the most aggressive brain tumor and is almost always fatal. These tumors are highly vascularized and angiogenesis is one of the pre-eminent mechanisms underlying their growth. Chronic arterial hypertension (CAH) is a common and worldwide pathology that markedlly alters the structure and function of the vasculature. Yet, essential hypertension is associated in the brain with potential locally impaired vasoreactivity, disturbed perfusion supply and hypoxia phenomena. Even though CAH is a global b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 68 publications
3
6
0
Order By: Relevance
“…In contrast to our hypothesis, we did not observe any temporal evolution in DKI parameters with tumor growth, as the tumor tissue clearly became more heterogenous with time, with increased necrotic areas. An increase in ADC over time has been reported by Letourneur et al 29 in a rat model with C6 glioma. However, no changes in ADC were observed in F98 tumors 29 or 9 L tumors 41 …”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…In contrast to our hypothesis, we did not observe any temporal evolution in DKI parameters with tumor growth, as the tumor tissue clearly became more heterogenous with time, with increased necrotic areas. An increase in ADC over time has been reported by Letourneur et al 29 in a rat model with C6 glioma. However, no changes in ADC were observed in F98 tumors 29 or 9 L tumors 41 …”
Section: Discussionsupporting
confidence: 54%
“…The increased MD may be due to increased extracellular diffusivity, or a significant increase in intracellular water diffusion due to cellular swelling. An increased mean diffusivity in tumors relative to the contralateral cortex was reported in rats with F98 and C6 glioma, 8–10,29 although some discrepancy exists, as another study reported decreased MD in C6 gliomas 30 . MRI diffusion parameters, such as MD and FA, have shown potential for predicting tumor grade, 31,32 treatment monitoring and prognosis 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Several mechanisms may explain the inverse associations observed for cancer in our study. In animal models, they observed significant attenuation of tumour growth in spontaneously hypertensive rats 27. The possible reason was partly due to the impaired angiogenesis as a result of chronic hypertension.…”
Section: Discussionmentioning
confidence: 97%
“…To the extent that glioblastoma stem cells are related to neural stem cells 41 hyperglycaemia may confer protection against glioblastoma. Another potential mechanism is inhibition of cerebral circulation associated with diabetes 42, 43 causing reduced glioma risk 44 . In addition, lower levels of insulin-like growth factor 1 (IGF-1) are found in diabetic than in non-diabetic serum 45 and tumour-associated macrophage derived IGF-1 may drive glioma recurrence 46 .…”
Section: Discussionmentioning
confidence: 99%